Kecerdasan Emosional Guru Dalam Memotivasi Belajar Siswa di SMP Negeri 24 Batanghari Jambi - Mutholib, Abdul (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2020)
This Article explain how emotional intellegence a educator energy able to give the maximal contribution in motivating to learn the student. Teacher is a professional educator with the especial duty educate, teaching, guiding, instructing, train, assessing, and evaluating competitor educated [at] band of education formal. intellegence a teacher in so many area very needed, one of them is emotional intellegence. Motivate the part of factor intern and represent psychological in its relation/link with the school activity. Educator energy as human resource representing big invesment asset which if exploited will become the very valuable capital in reaching the intention of education institute beside other capital source. Educator energy as especial component and handle of education calyx play role very signifikan of In education efficacy. For the reason, besides interest standard which must be owned by a teacher, emotional intellegence play role which enough significan in forming characteristic of a teacher remember with the the emotional intellegence, a teacher will be able to control its emotion and also able to play role its social with the teacher humanity, student, and also society